Motivation and Behavior of Farmers in Developing Swamp Buffalo in Rawas Ulu District, North Musi Rawas Regency - Setiawan, Bagus Dimas; Adlan, Zulhapi Utama (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2025)
This research aimed to analyze the potential of the base and the role of livestock resources in sustainable livestock development. This study was descriptive qualitative, used primary and secondary data that were obtained by survey methods through observation and interviews. This study was conducted in two stages, namely: 1) identification of development base areas using LQ analysis; and 2) analyzing the motivation and behavior of farmers and analyzing alternative solutions for swamp buffalo development. The data obtained were analyzed and tabulated which were presented in the form of qualitative descriptive analysis. The results of the study showed that the base areas for buffalo livestock development were in five villages, namely Teladas Village, Sungai Baung Village, Pulau Lebar Village, Lubuk Mas Village and Lesung Batu Muda Village. Buffalo farmers in Rawas Ulu District have sufficient motivation (score 35.2%) and have very poor behavior (knowledge 20.0%, attitude 30.4% and skills 14.5%. The results of the problem analysis contain two factors, namely internal and external factors. Internal factors consist of side businesses, human resources, and low-quality feed, while external factors consist of slow animal health services and many land conversions. Alternative solutions to internal problems include increasing business scale, increasing knowledge and skills in animal husbandry and planting superior forage, while solutions to external problems include adding manpower and animal health facilities and creating regulations for a system of rules and policies for buffalo livestock development areas.